Pengaruh Level Campuran Daun Lamtoro (Leucaena leucocephala) dan Daun Kelor (Moringa oleifera) Terhadap Berat, Ukuran dan Kandungan Nutrisi Maggot Lalat Tentara Hitam (Hermetia illucens) - Kristalia Sona; Gustaf Oematan; Twenfosel Dami Dato; Marthen L. Mullik (Animal Agricultura, 2023)
This experiment was designed to evaluate the effects of levels of a mixture of 50% chopped leucaena (Leucaena leucocephala) leave and 50% chopped moringa (Moringa oleifera)leave in the maggot’s growth media on weight, length, and nutrient content of maggot of black soldier fly(BSF). Exeperimental designed deployed was completely rendomized design (CRD) to test 4 treatments in 3 replicates. The treatments were standard growth media plus mixture of leucane-moringa leave at 10% (P1); 20% (P2); 30% (P3); 40% (P4). Standard growth media made of 10% yellow corn flour and 80% local rice bran. Measured variables were weight, length, and the content of dry matter (DM), crude protein (CP), and ether extract (EE) of maggot. The variables measured were done on 100 fully grown maggots (larvae 3) randomly taken as samples for each experimental unit. Collected data were subjected to analysis of variance using univariate general linear model for CRD to detect treatment effects at alfa value of 0.05. Duncan multiple range test was applied to assess treatment differences. Statistical analysis showed that levels of freshly-chopped leucaena and moringa leaves had insignificant effectschopped on fresh weight (0.9 – 1.1 g), length (11.6 mm – 13.8 mm), DM (41.3% - 50.3%) of maggot. In the contray increase level of mix leaves had a a highly significant effects on both CP (P=0.001) and EE (P0=001) with the hieghest value shown by treatment DN40. It could be summarised that mixing different levels of freshly chopped leucaena and moringa leaves in standard growth media will increase CP and EE content of the of larvae of black BSF.